Faktor-Faktor Yang Mempengaruhi Pemahaman Umkm Dalam Penerapan Laporan Keuangan Berdasarkan Sak Emkm Pada Umkm Di Pekanbaru - Febria, Indah; Aristi, Mentari Dwi; Fitriana, Nur (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This research aims to determine the factors that influence UMKM understanding of the application of financial reports based on SAK EMKM to UMKM in Pekanbaru. This type of research is quantitative research. Data analysis uses the multiple linear regression analysis method with understanding of UMKM as the dependent variable and four independent variables: level of education, business scale, business age and accounting knowledge. The research sample was 100 respondents. The results of this research state that the education level variable has a significant effect on the understanding of UMKM in UMKM in Pekanbaru. Business scale has a significant effect on understanding UMKM in UMKM in Pekanbaru. The age of the business has a significant effect on the understanding of UMKM in UMKM in Pekanbaru. Accounting knowledge has a significant influence on the understanding of UMKM in UMKM in Pekanbaru.